EFEKTIVITAS HYDROGEL LIDAH BUAYA (ALOE VERA) TERHADAP RUAM POPOK (DIAPERS RASH) PADA BAYI 0 – 12 BULAN - Haryono, Nathasia Elga; Hadisaputro, Suharyo; Suwondo, Ari (Media Penelitian dan Pengembangan Kesehatan, 2024)
Diaper rash occurs in approximately 25% of all babies born worldwide, with 6,840,507,000 experiencing diaper rash due to the use of diapers. The main causes of diaper rash are the growth of fungi and bacteria. Diaper rash can be treated using non-pharmacological therapy, one of which is the use of aloe vera gel. The purpose of this study is to prove the effectiveness of aloe vera gel in healing diaper rash in babies aged 0-12 months. This research was conducted in Kediri City from January to March. The sample in this study consisted of 36 baby respondents aged 0-12 months using random sampling. This study used a quasi-experimental design with a pretest-posttest control group design. The intervention group was given aloe vera hydrogel, while the control group was given zinc oxide ointment, then measured using the diaper dermatitis grading scale score. This study used the repeated measures ANOVA test. The results showed an average difference of 0.750 in the intervention group and 0.584 in the control group. It was shown that the effectiveness of healing diaper rash in the intervention group was 51.02%, and in the control group, it was 41.13%. Data analysis with a P-value < 0.05 indicated a difference in healing between the administration of zinc oxide and aloe vera in reducing diaper rash scores. The administration of aloe vera hydrogel is significantly effective in healing diaper rash in babies aged 0-12 months. Future research could use a narrower age range of babies.